The impact of administrative leadership in higher education institutions in light of technological progress and political changes in our Arab societies (قضايا سياسية, 2023)
The inevitable necessities to sustain societal development in proportion to the variables and internal and external challenges witnessed by the current era by adopting the foundations of analysis and identification of those challenges, where demographic changes in population, catastrophic health and economic crises, and the accompanying value and societal changes affected by external factors that swept the world between the characteristics of globalization to the technological revolution and electronic spaces The nature of the comprehensive change of lifestyles in its entirety led to a radical transformation of a digital, electronic and informational world, all of which necessitated a re-evaluation and construction of the basis for building societies, which is the educational process and its leadership The study aimed to identify the nature of leadership and the importance of their policies to change, reform and development in educational institutions which are dominated by stagnation, and limited aspirations and clarify how to put reform strategies into actual implementation through the performance of each aspect of society economic, educational, social and cultural role vital effective for change and building a better community.